2009
DOI: 10.3852/08-135
|View full text |Cite
|
Sign up to set email alerts
|

An expanded multilocus phylogeny does not resolve morphological species within the small-sporedAlternariaspecies complex

Abstract: Small-spored Alternaria species are a taxonomically challenging group of fungi with few morphological or molecular characters that allow unambiguous discrimination among taxa. The protein-coding genes most commonly employed in fungal systematics are invariant among these taxa, so noncoding, anonymous regions of the genome were developed to assess evolutionary relationships among these organisms. Nineteen sequence-characterized amplified regions (SCAR) were screened for phylogenetic utility by comparing sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
155
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(167 citation statements)
references
References 29 publications
6
155
1
5
Order By: Relevance
“…Se ha discutido su papel como endófito (Aly et al, 2008; Lahlali y Hijri, 2010; Kaur et al, 2013), saprófito o parásito de plantas vivas (Pitt y Hocking, 1997). La base de datos de hongos del Departamento de Agricultura de los Estados Unidos (USDA) presenta 4000 asociaciones de Alternaria con diferentes hospederos (Farr et al, 2013), convirtiéndose en uno de los géneros de hongos con más amplio rango de hospederos como patógeno de plantas (Andrew et al, 2009). Farr et al (1989), posicionan a Alternaria en el décimo lugar en términos del número total de plantas hospederas.…”
Section: Introductionunclassified
“…Se ha discutido su papel como endófito (Aly et al, 2008; Lahlali y Hijri, 2010; Kaur et al, 2013), saprófito o parásito de plantas vivas (Pitt y Hocking, 1997). La base de datos de hongos del Departamento de Agricultura de los Estados Unidos (USDA) presenta 4000 asociaciones de Alternaria con diferentes hospederos (Farr et al, 2013), convirtiéndose en uno de los géneros de hongos con más amplio rango de hospederos como patógeno de plantas (Andrew et al, 2009). Farr et al (1989), posicionan a Alternaria en el décimo lugar en términos del número total de plantas hospederas.…”
Section: Introductionunclassified
“…These patients are susceptible to infections from fungi rarely seen, or never reported as a human pathogen, which can cause identification problems for even the most experienced mycologists. Whereas mycologists in the past needed to be able to identify 50 commonly encountered fungi, and 300 total fungi that were pathogenic for humans, the number of potential fungal pathogens is likely many times what is described in textbooks, and will continue to grow as the severely immunosuppressed patient population continues to grow (Ajello and Hay 1998;Collier et al 1998;Andrew et al 2009). …”
mentioning
confidence: 99%
“…Rossman (2007) described the rationale for selection of ITS for barcoding the fungi but acknowledged that ITS does not work for some clearly recognizable species, and Seifert (2009) noted that additional barcode genes may be necessary for such fungi. Molecular studies using ITS rDNA (Kusaba and Tsuge 1995), protein coding housekeeping genes (Peever et al 2004), and anonymous open reading frames (ORF; Andrew et al 2009) sequence data, rDNA RFLPs (Kusaba and Tsuge 1994), and IGS restriction mapping (Hong et al 2005) from the smallspored Alternaria have demonstrated a low level of variability that do not support most segregations resulting from morphological, chemotaxonomic, and DNA fingerprinting studies. Kusaba and Tsuge (1995) went as far as to conclude that the small-spored species are all intraspecific variants of one species, A. alternata.…”
Section: Introductionmentioning
confidence: 99%